Biological effects of El Niño on the Galápagos penguin - Vergas, F; Harrison, S; Rea, S; Macdonald, D (Elsevier, 2006)
Long-term monitoring of physical and biological parameters is essential for understanding the effects of El Niño on bird populations, particularly for small or declining populations. We examined the biological effects of El Niño activity from 1965 to 2004 using instrumental sea-surface temperatures from the Galápagos Islands and 20 years of census counts of Galápagos penguin. Between 1965 and 2004, nine El Niño events were recorded of which two were strong and seven were weak. The two strong El Niño events of 1982-1983 and 1997-1998 were followed by crashes of 77% and 65% of the penguin population, respectively. The evidence suggest that the increased frequency of weak El Niño events limits population recovery. The 2004 penguin population is estimated to be at less than 50% of that prior to the strong 1982-1983 El Niño event. We discuss the biological effects of increased El Niño intensity and frequency within the context of a 6000-year record of El Niño influence and in the light of increasing anthropogenic threats operating after 1535, when the Archipelago was discovered by Europeans.